2014
DOI: 10.2135/cropsci2013.08.0526
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Tolerance‐Associated Quantitative Trait Loci in the Brundage × Coda Wheat Recombinant Inbred Line Population

Abstract: Freezing tolerance is an essential trait for winter wheat cultivars. A genetic analysis of a Brundage × Coda winter wheat recombinant inbred line (RIL) mapping population was undertaken to identify quantitative trait loci (QTL) associated with freezing tolerance. Five‐week to 6‐wk old, cold‐acclimated plants were frozen to –10.5, –11.5, or –12.5°C. The standardized mean percentage survival of all RILs within each temperature was 61, 44, and 28%, respectively. A total of 2391 polymorphic DNA markers including 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 83 publications
(209 reference statements)
4
22
0
Order By: Relevance
“…The reversal in the relative amounts of variance due to general and specific combining ability at the two test temperatures (Table ) suggested that some genes were active at one, but not both, of the two test temperatures. This observation is consistent with a previous report of molecular markers significantly associated with freezing tolerance at some, but not all, test temperatures (Case, Skinner, Garland‐Campbell, & Carter, ).…”
Section: Discussionsupporting
confidence: 93%
“…The reversal in the relative amounts of variance due to general and specific combining ability at the two test temperatures (Table ) suggested that some genes were active at one, but not both, of the two test temperatures. This observation is consistent with a previous report of molecular markers significantly associated with freezing tolerance at some, but not all, test temperatures (Case, Skinner, Garland‐Campbell, & Carter, ).…”
Section: Discussionsupporting
confidence: 93%
“…Lines from the AMP observed to have high tolerance to snow mold also possessed cold tolerance alleles on three C-repeat binding factor (CBF) loci (S Carle, unpublished data), suggesting that selecting lines that can survive cold temperatures could also result in selection for lines with snow mold tolerance. Major low-temperature tolerance QTL were previously identified in chromosome 5A (Båga et al, 2007; Case et al, 2014) and 5B (Zhao et al, 2013) near known freezing tolerance and vernalization genes, showing the relevance of these loci in winter survival, as well as tolerance to fungal diseases related with low temperature conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, QTL have been found on various chromosomes throughout the genome, as is the case in this study. For instance, three studies of freezing tolerance identified QTL on chromosomes 1A, 1D, 2A, 2B, 3A, 5A, 5B, 6A, 6D, and 7B ( Fowler et al 2016 ; Båga et al 2006 ; Case et al 2014 ). Each of these studies examined different freezing stress conditions, but they demonstrate the quantitative nature of freezing tolerance.…”
Section: Discussionmentioning
confidence: 99%